Qur’anic and Tafsir Virtual: Penyajian al-Qur’an dan Tafsir di Dunia Maya (Studi Kasus Kajian Tafsir Min Wahyil Qur’an Sayyid Husain Fadhlullah di Media YouTobe) - Ilma Amalia; Yayan Rahtikawati; Muhammad Faris Rasyadan (JURNAL ILMIAH PENDIDIKAN KEBUDAYAAN DAN AGAMA, 2024)
The Koran, as the main holy book of guidance for Muslims, is almost impossible to understand if it is not interpreted. Since ancient times, the transmission of interpretations of the Al-Qur'an has been carried out through various methods, including oral and written. Meanwhile, nowadays, times continue to develop, the delivery of interpretations of the Al-Qur'an is also developing through online audio-visual methods, especially through YouTube media. This article aims to analyze the interpretation of the Al-Qur'an through YouTube media in the book Min Wahyil Qur'an written by a contemporary tafsir scholar named Sayyid Husain Fadhlullah and how it influences the religious lives of his listeners. The method used in this research is a quantitative method by distributing questionnaires to 130 listeners of the Islamic Studies and JR TV channels. The research method is also equipped with qualitative methods by reviewing several library sources to enrich the reader's knowledge. The results of this research indicate that in quantity many listeners feel they want to change their attitudes and lifestyle in religion, especially after listening to the seventh series of Min Wahyil Qur'an tafsir studies with the theme: humans and religion.